Update on the Economic Impact of the 2014 Ebola Epidemic on Liberia, Sierra Leone, and Guinea - World Bank Group (Washington, DC, 2014)
The Ebola epidemic continues to cripple the economies of Liberia, Sierra Leone, and Guinea. The crisis is resulting in flat or negative income growth and creating large fiscal needs in all three countries, as they work to eradicate the virus. This update presents the World Bank s most recent analysis of the economic effects of the Ebola epidemic on the three countries. All three had been growing rapidly in recent years, and into the first half of 2014. But GDP growth estimates for 2014 have been revised sharply downward since pre-crisis estimates. Projected 2014 growth in Liberia is now 2.2 percent (versus 5.9 percent before the crisis and 2.5 percent in October). Projected 2014 growth in Sierra Leone is now 4.0 percent (versus 11.3 percent before the crisis and 8.0 percent in October). Projected 2014 growth in Guinea is now 0.5 percent (versus 4.5 percent before the crisis and 2.4 percent in October). The World Bank s October report on the economic impact of Ebola (report no. 91219 released at the 2014 Annual Meetings of the IMF and the World Bank) found that if the epidemic continues in the three worst-affected countries and spreads to neighboring countries, the two-year regional financial impact could range from a "low Ebola" estimate of $3.8 billion to a "high Ebola" estimate of $32.6 billion. These scale estimates of potential impact remain valid: the epidemic is not yet under control. Containment, combined with a full-fledged financial recovery effort to restart business activity and bring back investors, are now both therefore urgently needed for the region to improve on the downbeat forecasts in this update.